Bacterial attachment to polymeric materials correlates with molecular flexibility and hydrophilicity - Sanni, Olutoba; Chang, Chien-Yi; Anderson, Daniel G.; Langer, Robert; Davies, Martyn C.; Williams, Philip M.; Williams, Paul; Alexander, Morgan R.; Hook, Andrew L. (Wiley, 2015)
A new class of material resistant to bacterial attachment has been discovered that is formed from polyacrylates with hydrocarbon pendant groups. In this study, the relationship between the nature of the hydrocarbon moiety and resistance to bacteria is explored, comparing cyclic, aromatic, and linear chemical groups. A correlation is shown between bacterial attachment and a parameter derived from the partition coefficient and the number of rotatable bonds of the materials' pendant groups. This correlation is applicable to 86% of the hydrocarbon pendant moieties surveyed, quantitatively supporting the previous qualitative observation that bacteria are repelled from poly (meth)acrylates containing a hydrophilic ester group when the pendant group is both rigid and hydrophobic. This insight will help inform and predict the further development of polymers resistant to bacterial attachment.